SPH Success: A Program to Identify and Address Quantitative Preparedness in MPH Students - Tessa Bonney; Lauren Giacobbe (Pedagogy in Health Promotion, 2026)
Sustaining a diverse and effective public health workforce depends on an expanding and increasingly heterogeneous pipeline of graduate trainees. However, persistent structural inequities in academic preparedness highlight the need for intentional academic supports to ensure student success. In this paper, we describe the quantitative components of the School of Public Health (SPH) Success Program, a comprehensive academic support program to identify and assist master’s students needing remedial or supplemental support in foundational quantitative public health coursework. We analyzed data from two cohorts of first-year Master’s in Public Health students at a large public university in the United States to examine (1) the utility of a quantitative skills diagnostic assessment as an indicator of readiness for coursework, (2) engagement patterns with support resources, and (3) associations between resource use and course performance. Diagnostic scores were a strong and consistent predictor of exam performance, even after adjusting for prior academic preparation and sociodemographic characteristics, suggesting the assessment effectively captures applied quantitative readiness. Utilization of optional resources, including review modules, synchronous sessions, computing tools, and peer tutoring, was low and not significantly associated with improved exam outcomes, although modest positive trends were observed. These findings highlight a gap between identifying students in need and ensuring engagement with available supports. The program demonstrates the value of early, context-specific assessment in diverse graduate populations, particularly in the absence of standardized admissions metrics such as the Graduate Record Examination (GRE). Future efforts should focus on reducing structural barriers to resource access to promote equitable student success.